THE DEVELOPMENT OF INVENTORY, MONITORING AND INFORMATION NETWORKS SYSTEM OF FAUNAL DIVERSITY IN SOUTH SUMATRA - Yustian, Indra; Setiawan, Arum; Setiawan, Doni; Hanum, Laila; Dahlan, Zulkifli (BIOVALENTIA: Biological Research Journal, 2017)
Despite high attention and commitment of Indonesia in biodiversity conservation and its habitat, however, loss of biodiversity and habitat deforestation is also still high. Deforestation rate in Indonesia between period of 2000-2012 reach up 6.02 million ha, and approximately onethird of which is in Sumatra Island. As the fulfillment of CBD and Aichi targets, and in line with the mandate of the Law on the Conservation of Natural Resources and Ecosystems and IBSAP (Indonesian Biodiversity Strategy & Action Plan 2015-2020), we try to support the requires data as well as information on the current state of biodiversity. The aims are to develop an inventory system of biodiversity needed to establish baseline data on biodiversity including its conservation status in South Sumatra, develop a biodiversity monitoring system with qualitative parameters that can be used in the determination and monitoring of degradation rates of biodiversity, and the establishment of data management system and information network of fauna biodiversity in South Sumatera so that it can be utilized in monitoring and reporting of biodiversity at regional, national and international level at the international level. We conduct a comprehensive review of methods and techniques of inventory and monitoring of fauna biodiversity, especially those that have been done in the area of South Sumatra Province. We also analysis of data needs and information network of fauna biodiversity in South Sumatra. The results is shows in the web-application database, called the South Sumatran Biodiversity Information Networks, or SSBIN, and could preview at http://ssbin.unsri.ac.id/.Keywords: south sumatra, biodiversity, information, networks, SSBIN.